Multigenerational mistimed feeding drives circadian reprogramming with an impaired unfolded protein response - Huang, Kai; Zhang, Tao; Zhang, Wenjun; Gu, Yue; Yu, Pan; Sun, Lanqing; Liu, Zhiwei; Wang, Tao; Xu, Ying (Frontiers in Endocrinology, 2023)
Mistimed food intake in relation to the day/night cycle disrupts the synchrony of circadian rhythms in peripheral tissues and increases the risk of metabolic diseases. However, the health effects over generations have seldom been explored. Here, we established a 10-generation mouse model that was continuously fed with daytime-restricted feeding (DRF). We performed RNA-seq analysis of mouse liver samples obtained every 4 h over a 24 h period from F2, F5 and F10 generations exposed to DRF. Multigenerational DRF programs the diurnal rhythmic transcriptome through a gain or loss of diurnal rhythmicity over generations. Gene ontology (GO) analysis of the differential rhythmic transcriptome revealed that adaptation to persistent DRF is accompanied by impaired endoplasmic reticulum (ER) stress. Consistently, a substantially higher level of folding-deficient proinsulin was observed in F10 liver tissues than in F2 and F5 liver tissues following tail vein injection. Subsequently, tunicamycin induced more hepatocyte death in F10 samples than in F2 and F5 samples. These data demonstrate that mistimed food intake could produce cumulative effects over generations on ER stress sensitivity in mice.